Game Edukasi Untuk Menghafal Al-Quran Secara Sederhana Menggunakan Game Development Kit - Sopiyan Dalis; Heri Kuswara; Muhammad Idrus; Syamsul Bahri (Jurnal INSAN: Journal of Information System Management Innovation, 2022)
The Covid-19 pandemic has greatly impacted various aspects around the world, the education aspect has not escaped attention, forcing students and workers to do activities at home. And most students (especially Islamic schools) who when they enter school are memorizing the Al-Quran forget to return when they return to school. This is very unfortunate considering the virtue of memorizing the Qur'an is very great reward and also the goodness in it. Various methods are also widely used by parents and teachers, including through learning media in the form of games. Education Game "Ngaji Yuk" is based on the problem of memorizing the Al-Quran using a Game Development Life Cycle (GDLC) game development kit based with AppGameKit Classic programming language. This game is made so that players can memorize the Al-Quran in a very simple way, namely by choosing true or false statements in the questions that appear in front of the screen. It is hoped that this game can become an interactive game for everyone, especially children who are learning to memorize the Al-Quran. It is also hoped that this game can become a new learning medium that can help raise children's enthusiasm to memorize the Al-Quran with the main emphasis on always repeating memorization (Muroja'ah), with this learning being carried out properly, because this game has gone through the testing phase using Cyclomatic Complexity. From the results of the questionnaire that the author conducted with respondents aged 18 to 34 years who are still active with computers, it can be concluded that the game "Ngaji Yuk" has been developed according to user needs.